If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 + 3x + 2 + 2x + 3 + x + -4 = 5(2x + 2) Reorder the terms: 1 + 2 + 3 + -4 + 4x + 3x + 2x + x = 5(2x + 2) Combine like terms: 1 + 2 = 3 3 + 3 + -4 + 4x + 3x + 2x + x = 5(2x + 2) Combine like terms: 3 + 3 = 6 6 + -4 + 4x + 3x + 2x + x = 5(2x + 2) Combine like terms: 6 + -4 = 2 2 + 4x + 3x + 2x + x = 5(2x + 2) Combine like terms: 4x + 3x = 7x 2 + 7x + 2x + x = 5(2x + 2) Combine like terms: 7x + 2x = 9x 2 + 9x + x = 5(2x + 2) Combine like terms: 9x + x = 10x 2 + 10x = 5(2x + 2) Reorder the terms: 2 + 10x = 5(2 + 2x) 2 + 10x = (2 * 5 + 2x * 5) 2 + 10x = (10 + 10x) Add '-10x' to each side of the equation. 2 + 10x + -10x = 10 + 10x + -10x Combine like terms: 10x + -10x = 0 2 + 0 = 10 + 10x + -10x 2 = 10 + 10x + -10x Combine like terms: 10x + -10x = 0 2 = 10 + 0 2 = 10 Solving 2 = 10 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| =5(3+5) | | 7x^2+81=64 | | 5y^2+46y+105=0 | | 10+15x+3+2y+2x= | | 6y+4=12xfory | | 4x^(2/3)=108 | | Y=7(.98)x | | -5(0)-Y=5 | | 9x-4x+2+1=-3x+7x-5 | | ln(x-5)=ln(x+5)-ln(x-7) | | X=48-4p | | 5p+8+15p= | | 3y+3x=100 | | 4x-10=5x-x | | (-6x)-36=18-8x | | 0.50x+.20y=3.75 | | 14x-3=21 | | 2m+8+2(2m-3)=(m+3) | | 8x+11=118 | | -9x-21=-12-1 | | -40x+20=32x-26 | | 3x^3-11x^2+30=0 | | 0.5y=19.5 | | 15+3c+4d+2c= | | -5.895= | | 3(7-x)+6x= | | 27x+4=10 | | 0.375n=-0.75 | | P=3p-48 | | 9x+7(2x-4)=3-8x | | 3a-5=5a+3 | | 16x+24=15-20x |